Analytical Applications of Laplace Transforms in Solving Partial Differential Equations - Naima Mgasbi, (AlQalam Journal of Medical and Applied Sciences, 2025)
The Laplace transform is a powerful mathematical tool for converting partial differential equations into simpler algebraic equations. This transformation method is widely used in engineering, physics, and applied mathematics to solve problems involving time-dependent processes. Laplace transforms are a popular tool for solving initial-value problems. In most undergraduate courses, the use of tables, special theorems, partial fractions, and convolution is the method taught for finding the inverse. In most problems involving partial differential equations. Consider a function ￼f(t) ￼such that f(t)= 0 for t . Then the Laplace integral is defined as F(s) ￼ , the place transforms is the most commonly employed analytic technique after separation of variables. One of the key elements of this method involves finding the Laplace transform of u(x,t) and its partial derivatives, where u(x,t) denotes the solution to the partial differential equations.the Laform of u(x,t) ￼is d by the integral U(x,s) . F(s) . Clarify Laplace transforms may be used to solve linear partial differential equations. And the solution of linear partial differential equations by Laplace transforms is the most commonly employed analytic technique after separation of variables. One of the key elements of this method involves finding the Laplace transform of u(x,t) and its partial derivatives, where u(x,t) denotes the solution to the partial differential equations.the Laplace transform of u(x,t) is defined by the integral U(x,s) .